2017
DOI: 10.1016/j.psychres.2016.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors associated with negative affect in the friendships of children with ADHD: An exploratory study

Abstract: Our objective was to identify behaviors and contextual situations associated with negative affect observed in the interactions of children with and without ADHD and their real-life friends. We expected negative affect to be linked to rule violations and disagreements about the choice of games. Loss of game was associated with episodes of negative affect in a structured game. Negative appraisal of friend's ability was most frequently associated with negative affect during unstructured free play. Comparison chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…When students with ADHD make friends, they tend to be of poorer quality and less stable than their peers with TD. Moreover, a study with a group of ADHD students, along 6 months of duration (Normand et al, 2017), found that one in four students with ADHD lost his/her friend. Other authors (Hodgens et al, 2000) expressed that students with ADHD can experience social rejection within a few hours of meeting their peers.…”
Section: Discussionmentioning
confidence: 99%
“…When students with ADHD make friends, they tend to be of poorer quality and less stable than their peers with TD. Moreover, a study with a group of ADHD students, along 6 months of duration (Normand et al, 2017), found that one in four students with ADHD lost his/her friend. Other authors (Hodgens et al, 2000) expressed that students with ADHD can experience social rejection within a few hours of meeting their peers.…”
Section: Discussionmentioning
confidence: 99%
“…The social difficulties experienced by children with ADHD are much greater than those of their typically-developing peers [ 1 , 2 ]. Children with ADHD are often unpopular, frequently rejected by peers and have challenges in relationships with siblings and developing and maintaining friendships [ 3 , 4 ]. For example, friends of children with ADHD have reported more conflict in their relationships with children with ADHD overtime, where children with ADHD have not reported the same deterioration in their friendship quality over the same 6-month period [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties with empathy and perspective taking can explain the differences in the social play skills of children with ADHD [ 6 ], and can result in conflict, rejection, and poorer quality relationships with peers [ 3 , 5 ]. When playing with friends, children with ADHD have been observed to break more rules during competitive play, appear more self-focused when negotiating, and lack perspective-taking skills [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely to incivility, the construct OCB is positive in nature which has been demarcated by [12] as "individuals' behavior that is discretionary, not directly or explicitly recognized by the formal reward system, and that in aggregate promotes the effective functioning of the organization". Historically, organizations have attempted to ensure positive workplace outcomes by eliminating negative behaviors [13]. As per best of our knowledge, no study exists which elaborates the relationship of psychological capital and OCB, prosocial motivation and OCB, through the moderating role of workplace incivility.…”
Section: Introductionmentioning
confidence: 99%